2008
DOI: 10.1143/jjap.47.6754
|View full text |Cite
|
Sign up to set email alerts
|

Low-Time-Jitter Short-Pulse Generator Using Compact Gain-Switching Laser Diode Module With Optical Feedback Fiber Line

Abstract: On the basis of a self-pulse feedback mechanism, an ultralow-time-jitter and flexible repetitious rate optical pulse generator module with a simple and compact design was developed. Using a compact design self-seeding distributed feedback laser diode module, a low time jitter pulse on the order of sub-picoseconds was successfully observed within any modulation frequency range from 1 to 2 GHz. A pulse compression technique based on the nonlinear effect in optical fiber was used. A pulse width of 1.9 ps and a ji… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Nonaka et al successfully demonstrated a reduction of the timing jitter to about 0.5 ps by using the self-seeding optical feedback technique with a gain-switched semiconductor laser. 27) As a future work, it is recommended that a self-seeding feedback method be used for the femtosecond laser excitation source to dramatically reduce the timing jitter. This should result in a marked improvement of the effective bandwidth of the OSREFM technique.…”
Section: Resultsmentioning
confidence: 99%
“…Nonaka et al successfully demonstrated a reduction of the timing jitter to about 0.5 ps by using the self-seeding optical feedback technique with a gain-switched semiconductor laser. 27) As a future work, it is recommended that a self-seeding feedback method be used for the femtosecond laser excitation source to dramatically reduce the timing jitter. This should result in a marked improvement of the effective bandwidth of the OSREFM technique.…”
Section: Resultsmentioning
confidence: 99%
“…2. The novel GS-LD optical pulse source with a 2% partial reflector PR0 for low time jitter high-quality pulse is modulated for a tunable pulse generation with 1 to 2 GHz frequency repetitions [6] . The generated pulse width is about 20ps.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…The interrogation technique presented in this work is a wavelength-to-time domain analysis. The interrogation system is implemented with a gain-switching laser diode module [6]. This compact and reliable module uses an attached fiber code whose end is coated with diamond-like carbon (DLC) as a self-seeding pulse feedback circuit (figure 1 left).…”
Section: Pulse Generation and Interrogation Setupmentioning
confidence: 99%